THE USE OF NST TOEFL EXPLORER TO IMPROVE THE STUDENTS’ MASTERY IN GRAMMAR TOEFL - Barotun Mabaroh; Ninik Suryatiningsih (British : Jurnal Bahasa dan Sastra Inggris, 2019)
Optimizing information and communication technology (ICT) in language learning is best solution for boring conventional classes. It promises both lecturers and students better achievement in teaching and learning. Especially in Grammar for TOEFL (name of course taught in the fourth semester of English Education Study Program at STKPI PGRI Pasuruan), did the (lecturer) researcher decide to use NST TOEFL Explorer as one of ICT products to solve some instructional problems. In order to achieve the objective, thus this research was designed as a classroom action research and it used field notes, interview, and TOEFL test as instruments. The use of NST TOEFL Explorer did not simply require students to operate the application; therefore the research team seeked for and implemented working strategies to improve the students’ mastery in Grammar for TOEFL. The data from fieldnotes discovered the students were feeling enjoyable in using NST TOEFL Explorer. Moreover, from intervew, the students stated that learning grammar by NST TOEFL Explorer could make them motivated and confident in joining real TOEFL. The data collected by TOEFL test showed that the students could gain high scores. As a result, NST TOEFL Explorer could improve the students’ mastery in Grammar for TOEFL not only cognitively but also psychomotorically.